Pengembangan Asesmen Hots (Higher Order Thinking Skills) Untuk Mengukur Kemampuan Pemecahan Masalah Fisika Pada Materi Hukum Newton - Maulani, Nofrina; Linuwih, Suharto; Sulhadi, Sulhadi (UPEJ Unnes Physics Education Journal, 2021)
Higher Order Thinking Skills (HOTS) is higher-order thinking skills with higher thinking than memorizing facts or retelling something that is heard. In Higher Order Thinking Skills (HOTS) there are three categories: (1) transfer, (2) critical thinking, and (3) problem solving. In this study, the focus is on the third category, physics problem solving ability of students. The main analysis in developing the assessment is the value of validity, reliability, distinguishing power, and the level of difficulty of the questions. This study used a one shot case study method. Based on the results of the validity test using the help of software IBM SPSS Statistic Data Editor 22, the results of the questions are valid with R results> R Table. The value of R in the reliability test is 0.931. In the reliability test obtained, namely R results> R Table to get reliable test results. The difficulty level of questions with category 6 is good and 9 is very good. The distinguishing power of questions with category 3 difficult questions, 9 medium questions, and 3 easy questions. Newton's Law Assessment obtained valid and reliable questions that are used to measure the ability to solve physics problems.